Corrigendum: Reactive astrogliosis in the era of single-cell transcriptomics - Matusova, Zuzana; Hol, Elly M; Pekny, Milos; Kubista, Mikael; Valihrach, Lukas (Frontiers in cellular neuroscience, 2023)
[This corrects the article DOI: 10.3389/fncel.2023.1173200.].
Keywords: reactive astrogliosis; cell populations; single-cell RNA-seq; neuroinflammation; neurodegeneration; astrocytes; CNS diseases